Investigation of personal mobility devices (PMD) accidents I - Dheeraj Sharma S/O A K Jagdish Kumar (Nanyang Technological University, 2023)
The ability to carry a standing or seated rider is typical for Personal Mobility Devices (PMDs), which include electric bicycles (E-Bikes) and electric scooters (E-Scooters). The rise of E-Bikes and E-Scooter has introduced a new form of mobility to many cities worldwide, providing a convenient and affordable transportation option for short trips. Accidents involving E-bikes and E-Scooters often lead to serious injuries or even death. Scientific studies on PMD-pedestrian collisions have been lacking, especially for the effects on injuries of riders and pedestrians.